NON-FARM LIVELIHOOD DIVERSIFICATION AND SUB-SAHARAN AFRICA’S RURAL STRUCTURAL TRANSFORMATION: A REVIEW (FUDMA JOURNAL OF SCIENCES, 2022)
In the past, rural households’ were generally regarded as farmers, foresters or fisher-folk that participate only marginally in non-farm activities, except when they migrate out of rural areas. Nevertheless, despite the common generalization of the rural populace, especially in the developing world, as subsistence farmers, in certain cases a substantial portion of the income that accrue to rural households’ emanates from the rural non-farm sector. Hence, while agriculture has traditionally played a key role in the economy of developing countries, of late an increasing participation of farm households in the non-farm sector has been reported. Accordingly, one phenomenon that is gaining traction in the rural development parlance is the promotion of, and support for, non-farm livelihood diversification. A pertinent question to ask is whether this rising interest in the rural non-farm sector suggests that structural transformation away from agriculture has been taking place in Sub-Saharan Africa?
Keywords: Non-farm; Livelihood Diversification; Sub-Saharan Africa; Structural Transformation